2016
DOI: 10.1007/s11250-016-1030-9
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of effective population size and inbreeding in South African indigenous chicken populations: implications for the conservation of unique genetic resources

Abstract: Conservation of locally adapted indigenous livestock breeds has become an important objective in sustainable animal breeding, as these breeds represent a unique genetic resource. Therefore, the Agricultural Research Council of South Africa initiated a conservation programme for four South African indigenous chicken breeds. The evaluation and monitoring of the genetic constitution of these conservation flocks is important for proper management of the conservation programme. Using molecular genetic analyses, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…The local chickens are often kept by villagers under extensive management systems and without controlled breeding programs, but in some cases they are also kept in conservation facilities with the purpose to preserve their genetic architecture [20, 42, 49, 50]. Therefore, the high genetic diversity persists due to the fact that the pool for mating individual is generally larger, and hence a lower rate of inbreeding, and there is some exchange of genetic material by intercrossing of breeds, and little artificial selection is practiced [21, 40, 51]. Although the chicken breeds kept by German fancy breeders cover a wide spectrum of diversity overlapping with local breeds, the management followed by the fancy breeders only preserved the genetic relatedness of these breeds to their ancestral genetic background which, however, caused a drastic reduction in the level of genetic diversity within the breeds.…”
Section: Discussionmentioning
confidence: 99%
“…The local chickens are often kept by villagers under extensive management systems and without controlled breeding programs, but in some cases they are also kept in conservation facilities with the purpose to preserve their genetic architecture [20, 42, 49, 50]. Therefore, the high genetic diversity persists due to the fact that the pool for mating individual is generally larger, and hence a lower rate of inbreeding, and there is some exchange of genetic material by intercrossing of breeds, and little artificial selection is practiced [21, 40, 51]. Although the chicken breeds kept by German fancy breeders cover a wide spectrum of diversity overlapping with local breeds, the management followed by the fancy breeders only preserved the genetic relatedness of these breeds to their ancestral genetic background which, however, caused a drastic reduction in the level of genetic diversity within the breeds.…”
Section: Discussionmentioning
confidence: 99%
“…Lower degree of population stratification as well as high within-breed genetic diversity in African chickens are supported by analyses with microsatellite markers (Muchadeyi et al, 2007; Adebambo et al, 2010; Mtileni et al, 2011), mtDNA (Wani et al, 2014; Hassaballah et al, 2015; Eltanany and Hemeda, 2016) and genome-wide SNP chips (Khanyile et al, 2015a,b; Fleming et al, 2016, 2017). Reduced genetic diversity was, however, witnessed with conservation flocks in South Africa which represented a limited sample of the gene pool (Muchadeyi et al, 2007; Mtileni et al, 2016). Increasing expansion of the commercial chicken industry and intermixing of commercial hybrids with local strains in rural backyards are eroding the genetic uniqueness of native breeds and their potential to adapt to local conditions (reviewed by Eltanany et al, 2011).…”
Section: African Livestock Productivity In the Era Of Genomic Breedingmentioning
confidence: 99%
“…There is dearth of data on the extinction risk status of NICs but commentators agree that IC genetic resources are the most endangered and under conserved animal genetic resources [6,108,109] with extinction risk of 33% [110] and about 40% of breeds with unknown extinction risk status [111]. Studies have shown the dwindling frequency or apparent loss of rare NIC phenotypes such as the crested head, feathered shank or ptylopody, polydactyl or 5 toed, short flight feathered, and dwarf types, naked neck, frizzle, and silky, and major genes such as naked neck (Na), frizzle (F), dwarf (Dw), ptylopody (Fsh), and polydactyl (Po) believed to enhance survival and performance in tropical environments [6,16,112].…”
Section: Conservation Of Nigerian Indigenous Chicken Genetic Resources: Issues and Concernsmentioning
confidence: 99%
“…The concern about loss of IC genetic resources stems from the multifaceted economic, environmental and socio-cultural consequences highlighted by numerous studies [6,7,16,24,109,113]. a.…”
Section: Key Concerns On Loss Of Indigenous Chicken Genetic Resourcesmentioning
confidence: 99%
See 1 more Smart Citation